2018
DOI: 10.1371/journal.pone.0196597
|View full text |Cite
|
Sign up to set email alerts
|

Does the heritability of cognitive abilities vary as a function of parental education? Evidence from a German twin sample

Abstract: A well-known hypothesis in the behavioral genetic literature predicts that the heritability of cognitive abilities is higher in the presence of higher socioeconomic contexts. However, studies suggest that the effect of socioeconomic status (SES) on the heritability of cognitive ability may not be universal, as it has mostly been demonstrated in the United States, but not in other Western nations. In the present study we tested whether the importance of genetic and environmental effects on cognitive abilities v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…We found a main effect of SES on cognitive ability scores in the two younger cohorts, accompanied by a decrease of total phenotypic variance, as is typical in European samples (e.g., Bartels et al, 2009; Hanscombe et al, 2012; Spengler et al, 2018). However, in contrast to other European samples spanning middle childhood (Bartels et al, 2009; Hanscombe et al, 2012), our results in the youngest cohort support the Scarr-Rowe hypothesis.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We found a main effect of SES on cognitive ability scores in the two younger cohorts, accompanied by a decrease of total phenotypic variance, as is typical in European samples (e.g., Bartels et al, 2009; Hanscombe et al, 2012; Spengler et al, 2018). However, in contrast to other European samples spanning middle childhood (Bartels et al, 2009; Hanscombe et al, 2012), our results in the youngest cohort support the Scarr-Rowe hypothesis.…”
Section: Discussionsupporting
confidence: 73%
“…Further, our results are limited to fluid cognitive abilities. Although existing evidence is mixed, some studies show differing results for abilities that are presumably more closely related to family SES (Grant et al, 2010; Spengler et al, 2018). Our results may also be limited by the fact that the ‘TwinLife’ sample is somewhat underrepresented with regard to lower SES levels compared to the German population (see Lang & Kottwitz, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rosalind et al, (2018) reported that cognitive abilities of twins were heritable and observed that the genetic and environmental influences on different developmental patterns of verbal and non-verbal cognitive abilities of twins from the age group 7 to 12 years. Spengler et al, (2018) investigated that genetic and environmental effects on verbal cognitive abilities of twins in the age of 7-14 years and reported that verbal cognitive ability and nonverbal ability indicated no significant interaction with parental education, while verbal abilities showed a significant interaction with parental education. The verbal abilities were more influenced by genetic factors.…”
Section: Heritability Estimates For Behavioural Aspectsmentioning
confidence: 99%